2018
DOI: 10.1002/dys.1585
|View full text |Cite
|
Sign up to set email alerts
|

The modality and redundancy effects in multimedia learning in children with dyslexia

Abstract: The present study aimed to examine the modality and redundancy effects in multimedia learning in children with dyslexia in order to find out whether their learning benefits from written and/or spoken text with pictures. We compared study time and knowledge gain in 26 11‐year‐old children with dyslexia and 38 typically reading peers in a within‐subjects design. All children were presented with a series of user‐paced multimedia lessons in 3 conditions: pictorial information presented with (a) written text, (b) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
(90 reference statements)
3
13
1
1
Order By: Relevance
“…Results showed that audio-support has the potential to improve comprehension in students with decoding difficulties. Recent research in primary school children with dyslexia found no additional benefit of the use of audio-support on comprehension (Knoop-van Campen et al, 2018. Furthermore, in university students (with and without dyslexia), it was demonstrated that audio-support resulted in different reading behaviour (more focus on the supporting illustration and less on the written text) and, moreover, lead to lower comprehension (Knoop-van Campen et al, 2020).…”
Section: Reading Comprehension In Students With Dyslexiamentioning
confidence: 97%
“…Results showed that audio-support has the potential to improve comprehension in students with decoding difficulties. Recent research in primary school children with dyslexia found no additional benefit of the use of audio-support on comprehension (Knoop-van Campen et al, 2018. Furthermore, in university students (with and without dyslexia), it was demonstrated that audio-support resulted in different reading behaviour (more focus on the supporting illustration and less on the written text) and, moreover, lead to lower comprehension (Knoop-van Campen et al, 2020).…”
Section: Reading Comprehension In Students With Dyslexiamentioning
confidence: 97%
“…Also, Henry, Castek, O'Byrne, and Zawilinski (2012) and Castek et al (2011) have suggested that support from images, videos, and audio files can benefit struggling readers learning in a multimedia environment. This suggestion was supported by Knoop-van Campen, Segers, and Verhoeven (2018), who studied the modality effect (the assumption that learning gain is larger when verbal input is presented auditorily than as text), and the redundancy effect, for children with dyslexia learning in a multimedia environment. These authors found that children with dyslexia spent more time learning in a text condition than in both audio and text-and-audio conditions.…”
Section: Potential Benefitsmentioning
confidence: 88%
“…When students learning English as a second language were taught scientific concepts in an animated narration condition with subtitles or in an animated narration-only condition, students who received the multimedia instruction performed significantly better. Similarly, Knoop-van Campen, Segers, and Verhoeven (2018) found a reversed redundancy effect for children with dyslexia.…”
Section: Limitations and Direction For Future Researchmentioning
confidence: 88%